The way we mean now: on the poetics of Susan Howe, Lyn Hejinian, and Occupy Wall Street. Issue 7 (10th November 2017) - Phillis, Jen Hedler
ABSTRACT: This article examines the poetry and critical writing of Susan Howe and Lyn Hejinian, read in the context of the politics of Occupy Wall Street. While Howe has long been thought an important, if peripheral, member of the Language writing group, I argue that her poetry is fundamentally opposed to the central beliefs of the Language writers, as it is uninterested in the participation of the reader in the meaning of the poem or the participation of the poem in contemporary politics. Lyn Hejinian's work, in contrast, is designed to develop a quotidian creative practice that merges aesthetics and politics. It is no surprise, then, that Hejinian has been actively involved in and published articles detailing Occupy's political formation. Both her poetry and Occupy's politics depend on a presentist temporality, which prevents Occupy from producing the conditions by which its utopian premise might be fulfilled. The very aesthetic commitments that make Howe appear in opposition to the participatory aesthetics and politics of Occupy entail a far more progressive and utopian vision of the future and fill in the gap in their political theory.